New liberal arts education in Japan - Namai, Kenichi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Japan has a long history of liberal arts education, whose main mission has been to accommodate domestic academic needs by offering various courses solely in the Japanese language. At the turn of the century, however, it saw the advent of a new type of liberal arts education that is characterized by its international focus and small-size seminars. In stark contrast with the traditional type, this new type typically offers university courses in English and teaches both Japanese and international students in the same classroom. This paper explains merits of this type of education from the perspective of developing well-rounded Japanese individuals who can adequately handle cross-cultural communication, fully utilizing practical skills of English that they acquire during the four years of undergraduate studies.